Investigating apparent commonalities between the apocalyptic traditions from iIan and second-temple Judaism - Van der Merwe, Jeanne (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (Ancient Studies))--Stellenbosch University, 2008.